Legal Protection of a Notary Against the Crime of Falsification of Information in an Authentic Deed According to Law Number 30 of 2004 concerning the Position of a Notary - Roland Nofenick; Gavriele Liberty; Deco Hosenio; Clarissa Mayella; Shavira Ardita; Jeane Neltje Saly (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Notary is a public official appointed by the government to carry out the task of making authentic deeds or other legal actions in accordance with applicable statutory provisions. The functions of a notary vary depending on the legal system in each country. In some cases where documents notarized by a notary contain false or fraudulent information, the notary may be subject to legal sanctions. Law Number 2 of 2014 concerning the Office of a Notary indeed regulates the duties of a notary in certifying detailed documents provided by clients, as stated in Article 16 paragraph (1) letter (f). Notary Honorary Council (MKN) is an institution established under UUJN and has a role in carrying out ethical oversight of notaries. However, MKN is not an institution that provides direct legal protection in criminal cases. MKN's duties are more focused on the ethical and disciplined aspects of the notary profession. This research uses a normative legal approach and departs from a void of norms, the aim of the research can be to identify and analyze the legal protection available to notaries in contexts where there are no specific provisions regarding the matter. The results of the study show that there is legal protection for notaries, namely stated in article 66 paragraph (1) UUJN by establishing a new legal protection institution for Notaries, namely MKN, law enforcers when summoning them must ask permission from the Notary Honorary Council.